THE STORY OF THE BC FAMILY JUSTICE INNOVATION LAB - Morley, Jane; Boyle, Kari D. (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2017)
Many in the justice system know that fundamental change is needed but few know the best way to do it.  Previous attempts using strategic planning approaches have not achieved meaningful change.  Something different is needed.  The BC Family Justice Innovation Lab (the Lab) is experimenting with a different approach drawing on complexity science, the experience of other jurisdictions and disciplines and incorporating human-centred design as a way of focusing on the well-being of families going through the transition of separation and divorce.  This article is the story of the first few years of the Lab’s life.  It has been a fascinating and challenging path so far, and it remains to be seen whether it will ultimately succeed. The story is offered so that others with similar ambitions can learn from the Lab’s experience – its successes and its failures.  It is the nature and strength of stories that the reader will take from them what they will. For the authors, one overriding theme that emerges from this story is that transforming a complex social system, such as the family justice system in British Columbia, requires embracing the complexity of paradox and refusing to be defeated by the tension of opposites and a multitude of wicked, unanswerable questions.